Diagnóstico Y Mejoramiento Del Sistema De Acueducto Para La Vereda De Gualcan; Municipio Páez – Cauca (2023)
The main objective of the project "Diagnosis and Improvement of the Aqueduct System for the Vereda de Gualcan; Páez Municipality - Cauca" is to address the existing challenges in the supply of drinking water in the community of Gualcan, located in the Páez municipality of the department of Cauca. This project arises from the prevailing need to guarantee continuous and safe access to quality water for the residents of the village, as well as to improve the community's knowledge capacity to face future eventualities related to water.